Improving diabetes care in rural areas: a systematic review and meta-analysis of quality improvement interventions in OECD countries - Ricci-Cabello, I; Ruiz-Perez, I; Rojas-García, A; Pastor, G; Gonçalves, D (Public Library of Science, 2013)
Background and Aims Despite well documented disparities in health and healthcare in rural communities, evidence in relation to quality improvement (QI) interventions in those settings is still lacking. The main goals of this work were to assess the effectiveness of QI strategies designed to improve diabetes care in rural areas, and identify characteristics associated with greater success. Methods We conducted a systematic review and meta-analysis. Systematic electronic searches were conducted in MEDLINE, EMBASE, CINAHL, and 12 additional bibliographic sources. Experimental studies carried out in the OECD member countries assessing the effectiveness of QI interventions aiming to improve diabetes care in rural areas were included. The effect of the interventions and their impact on glycated hemoglobin was pooled using a random-effects meta-analysis. Results Twenty-six studies assessing the effectiveness of twenty QI interventions were included. Interventions targeted patients (45%), clinicians (5%), the health system (15%), or several targets (35%), and consisted of the implementation of one or multiple QI strategies. Most of the interventions produced a positive impact on processes of care or diabetes self-management, but a lower effect on health outcomes was observed. Interventions with multiple strategies and targeting the health system and/or clinicians were more likely to be effective. Six QI interventions were included in the meta-analysis (1,496 patients), which showed a significant reduction in overall glycated hemoglobin of 0.41 points from baseline in those patients receiving the interventions (95% CI -0.75% to -0.07%). Conclusions This work identified several characteristics associated with successful interventions to improve the quality of diabetes care in rural areas. Efforts to improve diabetes care in rural communities should focus on interventions with multiple strategies targeted at clinicians and/or the health system, rather than on traditional patient-oriented interventions.